Extension of helix 12 in Munc18-1 induces vesicle priming - Munch, Anders S.; Kedar, Girish H.; Weering, Jan R. T. van; Vazquez-Sanchez, Sonia; He, Enqi; André, Timon; Braun, Thimo; Söllner, Thomas; Verhage, Matthijs; Sørensen, Jakob B. (The journal of neuroscience, 2016)
Munc18-1 is essential for vesicle fusion and participates in the docking of large dense-core vesicles to the plasma membrane. Recent structural data suggest that conformational changes in the 12th helix of the Munc18-1 domain 3a within the Munc18-1:syntaxin complex result in an additional interaction with synaptobrevin-2/VAMP2 (vesicle-associated membrane protein 2), leading to SNARE complex formation. To test this hypothesis in living cells, we examined secretion from Munc18-1-null mouse adrenal chromaffin cells expressing Munc18-1 mutants designed to either perturb the extension of helix 12 (Δ324-339), block its interaction with synaptobrevin-2 (L348R), or extend the helix to promote coil-coil interactions with other proteins (P335A). The mutants rescued vesicle docking and syntaxin-1 targeting to the plasma membrane, with the exception of P335A that only supported partial syntaxin-1 targeting. Disruptive mutations (L348R or Δ324-339) lowered the secretory amplitude by decreasing vesicle priming, whereas P335A markedly increased priming and secretory amplitude. The mutants displayed unchanged kinetics and Ca2+ dependence of fusion, indicating that the mutations specifically affect the vesicle priming step. Mutation of a nearby tyrosine (Y337A), which interacts with closed syntaxin-1, mildly increased secretory amplitude. This correlated with results from an in vitro fusion assay probing the functions of Munc18-1, indicating an easier transition to the extended state in the mutant. Our findings support the notion that a conformational transition within the Munc18-1 domain 3a helix 12 leads to opening of a closed Munc18-1:syntaxin complex, followed by productive SNARE complex assembly and vesicle priming. - SIGNIFICANCE STATEMENT The essential postdocking role of Munc18-1 in vesicular exocytosis has remained elusive, but recent data led to the hypothesis that the extension of helix 12 in Munc18 within domain 3a leads to synaptobrevin-2/VAMP2 interaction and SNARE complex formation. Using both lack-of-function and gain-of-function mutants, we here report that the conformation of helix 12 predicts vesicle priming and secretory amplitude in living chromaffin cells. The effects of mutants on secretion could not be explained by differences in syntaxin-1 chaperoning/localization or vesicle docking, and the fusion kinetics and calcium dependence were unchanged, indicating that the effect of helix 12 extension is specific for the vesicle-priming step. We conclude that a conformational change within helix 12 is responsible for the essential postdocking role of Munc18-1 in neurosecretion.
Gesehen am 02.10.2020